COMPARATIVE STUDY ON ANTIBACTERIAL ACTIVITY OF CHAMOMILE OIL AND LEMONGRASS OIL ON ORAL PATHOGENS. - R.Kushali,; Geetha R.V, (International Journal of Psychosocial Rehabilitation, 2020)
Chamomile essential oil is being used for a variety of ailments like indigestion, nausea, ulcers, gives relief from anxiety, helps in depression, helps in skin irritation.Lemon grass oil is another essential oil used for studies which shows properties like reducing bodily aches. This essential oil shows antibacterial activities and helps against skin infections, pneumonia, blood infection and intestinal infections.It also has antifungal properties and anti inflammatory properties against oral pathogens like , Streptococcus mutants, Actinomyces,lactobacillus, peptococcus,Enterococcus faecalis.The method used was disc- diffusion method . The essential oils were obtained commercially and the anti-bacterial activity was compared by adding the oils in different concentrations in25 μl , 50μl , 100 μl and 50μl of 0.2% of chlorhexidine. The oral pathogens used for the study are Streptococcus mutans , Enterococcus faecalis and Lacto bacillus.The results show that lemon grass oil shows a wide zone of inhibition on 100 μl of 26mm followed by chamomile oil which shows zone of inhibition for 24 mm on 100 μl. The zone of inhibition was compared to 0.2% of chlorhexidine which showed a zone of inhibition of 25mm on 50 μl. Both the oils inhibited Streptococcus mutans.From the study it can be concluded that lemon grass oil and chamomile oil can be used as mouthwashes or constituents of mouthwashes as they show high percentage of inhibition of bacteria growth in various concentrations. Also when compared to the standard 0.2% of chlorhexidine , the essential oils were effective in inhibiting for pathogens of the oral cavity.